Toward a patient-specific tissue engineered vascular graft. (15th March 2018) - Best, Cameron; Strouse, Robert; Hor, Kan; Pepper, Victoria; Tipton, Amy; Kelly, John; Shinoka, Toshiharu; Breuer, Christopher
Integrating three-dimensional printing with the creation of tissue-engineered vascular grafts could provide a readily available, patient-specific, autologous tissue source that could significantly improve outcomes in newborns with congenital heart disease. Here, we present the recent case of a candidate for our tissue-engineered vascular graft clinical trial deemed ineligible due to complex anatomical requirements and consider the application of three-dimensional printing technologies for a patient-specific graft. We 3D-printed a closed-disposable seeding device and validated that it performed equivalently to the traditional open seeding technique using ovine bone marrow–derived mononuclear cells. Next, our candidate's preoperative imaging was reviewed to propose a patient-specific graft. A seeding apparatus was then designed to accommodate the custom graft and 3D-printed on a commodity fused deposition modeler. This exploratory feasibility study represents an important proof of concept advancing progress toward a rationally designed patient-specific tissue-engineered vascular graft for clinical application.